2018
DOI: 10.1371/journal.pone.0203083
|View full text |Cite
|
Sign up to set email alerts
|

Selective ablation of the ligament of Marshall reduces ischemia and reperfusion-induced ventricular arrhythmias

Abstract: Cardiac sympathetic tone overdrive is a key mechanism of arrhythmia. Cardiac sympathetic nerves denervation, such as LSG ablation or renal sympathetic denervation, suppressed both the prevalence of VAs and the incidence of SCD. Accumulating evidence demonstrates the ligament of Marshall (LOM) is a key component of the sympathetic conduit between the left stellate ganglion (LSG) and the ventricles. The present study aimed to investigate the roles of the distal segment of LOM (LOMLSPV) denervation in ischemia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…(2008) found that neural activation of the LOM LSPV by norepinephrine injection caused accelerated junctional rhythms, idioventricular rhythms, and VT. LOM LSPV ablation reduced VAs occurrence induced by cesium combined with LSG stimulation in canines ( Wang et al., 2016a ). Additionally, in dogs with acute MI or ischemia-reperfusion models, LOM LSPV ablation ameliorated the prevalence of VAs by reducing sympathetic tone ( Liu et al., 2018 ; Ma et al., 2018 ). Therefore, the LOM may serve as a sympathetic conduit between the LSG and ventricles.…”
Section: Methods Of Autonomic Modulation For Treating Ventricular Arrmentioning
confidence: 99%
“…(2008) found that neural activation of the LOM LSPV by norepinephrine injection caused accelerated junctional rhythms, idioventricular rhythms, and VT. LOM LSPV ablation reduced VAs occurrence induced by cesium combined with LSG stimulation in canines ( Wang et al., 2016a ). Additionally, in dogs with acute MI or ischemia-reperfusion models, LOM LSPV ablation ameliorated the prevalence of VAs by reducing sympathetic tone ( Liu et al., 2018 ; Ma et al., 2018 ). Therefore, the LOM may serve as a sympathetic conduit between the LSG and ventricles.…”
Section: Methods Of Autonomic Modulation For Treating Ventricular Arrmentioning
confidence: 99%
“…The autonomic nervous system consists of the sympathetic and parasympathetic nervous systems, which counteract each other to maintain a dynamic balance in a normal physiological state. Studies have indicated a substantial increase in sympathetic activity during IR in the heart, kidney, and other organs, leading to an imbalance of the autonomic nervous system [ [76] , [77] , [78] , [79] ]. During myocardial IR in mice, rats, and dogs, norepinephrine (NE) and epinephrine concentrations in plasma and paraventricular nucleus increased significantly, accompanied by cardiac sympathetic nerve activation [ [76] , [77] , [78] ].…”
Section: Autonomic Nervous System and Irimentioning
confidence: 99%
“…Studies have indicated a substantial increase in sympathetic activity during IR in the heart, kidney, and other organs, leading to an imbalance of the autonomic nervous system [ [76] , [77] , [78] , [79] ]. During myocardial IR in mice, rats, and dogs, norepinephrine (NE) and epinephrine concentrations in plasma and paraventricular nucleus increased significantly, accompanied by cardiac sympathetic nerve activation [ [76] , [77] , [78] ]. There was also a significant rise in the incidence of malignant arrhythmias, such as ventricular extrasystole and ventricular tachycardia [ 76 , 77 , [80] , [81] , [82] ].…”
Section: Autonomic Nervous System and Irimentioning
confidence: 99%
See 2 more Smart Citations